O horror da sexualidade em pague para entrar, reze para sair - SOUZA, Leandro Cardoso de (2016)
This work proposes an analysis of the film Pay to enter, reze to leave (The Funhouse, 1981), directed in the USA by the filmmaker Tobe Hooper. The purpose of the analysis is to observe how this adolescent horror film constructs a depiction of young sexual initiation filled with horrific suggestions that point to a nuisance about sex that is a hallmark of the adolescent horror of the 1980s. work draws on a detailed description of the film, relating it to the horror film history of the 1980s and to reflections on the genre as Robin WOOD (1979), Carol CLOVER (2002) and Adriene BOUTANG (2014).